2019
DOI: 10.1177/0093854819891460
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Psychopathy and the Trait Meta-Mood Scale in Incarcerated Males: A Combined Latent Variable- and Person-Centered Approach

Abstract: The present study sought to replicate and extend current knowledge on the relevance of emotion regulation (ER) for psychopathy. In a large sample of incarcerated adult males ( N = 578), latent profile analysis (LPA) and structural equation modeling (SEM) were employed to examine person- and variable-centered associations between self-reported ER and both self-report and clinical ratings of psychopathy. With LPA, participants were classified into three profiles corresponding to low, medium, and high ER. The low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 74 publications
6
14
0
Order By: Relevance
“…EI has been observed as negatively correlating with antisocial behaviors (Mavroveli & Sánchez-Ruiz, 2011), and fewer EI skills have been identified in adolescent offenders than in their normative peers (Contreras & Cano, 2016;Fariña et al, 2008;Hayes & Reilly, 2013;Kahn et al, 2016). In adults, it has been observed that when emotional regulation problems increase, more psychopathic traits are manifested in the affective, lifestyle, and antisocial domains (Garofalo et al, 2020). Socialization problems and trauma have also been identified as affecting EI in male offenders (Wang et al, 2019).…”
Section: Emotional Intelligence and Empathy In Offendersmentioning
confidence: 99%
“…EI has been observed as negatively correlating with antisocial behaviors (Mavroveli & Sánchez-Ruiz, 2011), and fewer EI skills have been identified in adolescent offenders than in their normative peers (Contreras & Cano, 2016;Fariña et al, 2008;Hayes & Reilly, 2013;Kahn et al, 2016). In adults, it has been observed that when emotional regulation problems increase, more psychopathic traits are manifested in the affective, lifestyle, and antisocial domains (Garofalo et al, 2020). Socialization problems and trauma have also been identified as affecting EI in male offenders (Wang et al, 2019).…”
Section: Emotional Intelligence and Empathy In Offendersmentioning
confidence: 99%
“…The implications of these findings for the study of psychopathy within a forensic setting merit comment. Seven of the included studies used forensic samples incorporating a mix of AEI and TEI measures, and either the PCL-R (Hare, 1991, 2003) or Lilienfeld and Andrews’ (1996) PPI-R (Copestake et al, 2013; Curci et al, 2017; Ermer et al, 2012; Garofalo et al, 2020; Malterer et al, 2008; Pham et al, 2010; Ray et al, 2011). The pattern of results demonstrates a negative association between secondary psychopathy and EI when AEI measures are used, and generally a positive association when TEI measures are used.…”
Section: Resultsmentioning
confidence: 99%
“…However, a considerable body of research supports a four-factor model of psychopathy (e.g., Neumann et al, 2007, 2015), in which psychopathy is conceptualized as a multifarious construct comprising interpersonal, affective, lifestyle, and antisocial facets (Hare & Neumann, 2008). Given that these facets have been differentially associated with individual differences in cognitive and emotional processing (e.g., Garofalo et al, 2020; Vitacco et al, 2005), it is possible that different facets of psychopathy contribute in unique ways to the complex associations between psychopathy and different aspects of moral-dilemma judgments.…”
mentioning
confidence: 99%